Analysis of The Application Information Technology On Employee Work Productivity PT Rajendra Kesatria Perkasa Depok - Rini Septiowati (International Institute for Advanced Science & Technology (IIAST), 2026)
The rapid development of Information Technology (IT) has significantly influenced organizational performance, particularly in enhancing employee productivity, efficiency, and work quality. This study focuses on PT Rajendra Ksatria Perkasa in Depok with the aim of analyzing how the implementation of IT affects employee work productivity. A qualitative research design was employed through a case study approach combined with SWOT analysis, with data collected from in-depth interviews and relevant document analysis. The findings reveal that optimal utilization of IT contributes positively by increasing efficiency and strengthening team collaboration. Nevertheless, challenges remain, including the limited understanding among employees regarding effective technology use. Opportunities also arise as digital advancements provide broader access to innovation in the workplace, yet threats such as decreased focus due to uncontrolled use of technology must be anticipated. Overall, the results highlight the importance of strategic management in maximizing the benefits of IT while simultaneously addressing its potential weaknesses and risks. Furthermore, the study provides a foundation for future research on the broader implications of digitalization within organizational contexts.